Sorghum 2-Dimensional Proteome Profiles and Analysis of HSP70 Expression Under Salinity Stress - Bongani K. Ndimba,; Ludivine A. Thomas,; Rudo Ngara, (Agriculture and Natural Resources, 2010)
Sorghum (Sorghum bicolor), a drought-tolerant cereal, is the second most important grain crop in Africa after maize (Zea mays). In this study, sorghum proteomes from whole plant organs (leaves, sheaths and roots), as well as cell suspension culture systems were resolved successfully using gelbased proteomics tools. Total soluble proteins (TSP) were extracted from leaves, sheaths and roots, as well as cultured cells. These proteomes were resolved via two-dimensional polyacrylamide gel electrophoresis (2D-PAGE). Proteins were visualized by Coomassie Brilliant Blue (CBB) and identified by MALDI-TOF mass spectrometry (MS). Five different proteomes were studied: total soluble proteome and secretome from cell suspension culture, as well as leaf, sheath and root proteomes from whole plants. Unique protein expression profiles were observed for each of the five proteomes, suggesting specialization of the proteins. Western blot analysis indicated that, as expected, HSP70 protein expression was induced in the roots of the experimental material following salt stress treatments. Cell suspension cultures provide a special research material, particularly for studies related to secreted proteins. The expected secretion of an alpha-galactosidase was also observed. On completion of spot mapping and identification, this proteome data could be used as a research/reference resource by many sorghum and grain scientists worldwide.